2014
DOI: 10.1155/2014/561920
|View full text |Cite
|
Sign up to set email alerts
|

Bromate Removal from Water Using Doped Iron Nanoparticles on Multiwalled Carbon Nanotubes (CNTS)

Abstract: The raw carbon nanotubes (CNTs) were prepared by the floating catalyst chemical vapor deposition method. The raw carbon nanotubes were functionalized, impregnated with iron nanoparticles, and characterized using high resolution transmission electron microscopy (HRTEM), scanning electron microscopy with energy dispersive spectroscopy (SEM-EDS), Fourier transform infrared spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), and thermogravimetric analysis (TGA). The three types of these multiwalled carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 27 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…Further applications are currently focused on environmental remediation due to their likely performance in contamination removal and toxicity mitigation (Gavaskar et al, 2005;Tratnyek and Johnson, 2006). Ironbased ENPs stimulated research for engineering applications especially for treating polluted water and groundwater (Tang and Lo, 2013) including both inorganics and organics (Crane and Scott, 2014;Mar Gil-Díaz et al, 2014;Zeino et al, 2014). Their impact is still highly empirical and limited to nanoparticles' elemental composition, size and stability showing both positive and negative effects.…”
Section: Introductionmentioning
confidence: 99%
“…Further applications are currently focused on environmental remediation due to their likely performance in contamination removal and toxicity mitigation (Gavaskar et al, 2005;Tratnyek and Johnson, 2006). Ironbased ENPs stimulated research for engineering applications especially for treating polluted water and groundwater (Tang and Lo, 2013) including both inorganics and organics (Crane and Scott, 2014;Mar Gil-Díaz et al, 2014;Zeino et al, 2014). Their impact is still highly empirical and limited to nanoparticles' elemental composition, size and stability showing both positive and negative effects.…”
Section: Introductionmentioning
confidence: 99%
“…The second main strategy, i.e., removal of bromate by adsorption, has become a prominent research topic recently due to its convenience and low cost, and many kinds of material have been tested. These include carbon-based materials, such as ordered mesoporous carbon (Xu et al 2014), doped iron nanoparticles on multi-walled carbon nanotubes (Zeino et al 2014), and nanoscale zero-valent iron supported on modified activated carbon (Wu et al 2013). However, most of these absorbents are relatively expensive and have limited potential for application.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that, with increase in the adsorbent dosage, the adsorption efficiency has increased. This can be justified due to the availability of more active adsorption sites at higher adsorbent dosage [17,26]. Figure 9 represents the pH effect on removal efficiency and adsorption capacity of iron oxide nanoparticles impregnated CNTs.…”
Section: Effect Of Adsorbent Dosagementioning
confidence: 99%
“…The most common materials reported are activated carbon [4], raw carbon nanotubes [13], and modified carbon nanotubes [14][15][16] for removal of BTEX. Recently, metal oxide impregnated CNTs have shown better adsorption capacity and removal efficiency as compared to raw CNTs and other adsorbents for different pollutants [17][18][19][20][21][22]. Novel carbon nanotube membranes are also appealing candidates for a number of applications in water treatment [23,24].…”
Section: Introductionmentioning
confidence: 99%